A Randomized, Controlled Trial of Treat-and-Extend vs. Pro Re Nata Regimen for Neovascular Age-Related Macular Degeneration - Jia, Huixun; Lu, Bing; Yuan, Yuanzhi; Yuan, Fei; Li, Lei; Song, Yanping; Rong, Ao; Zhou, Minwen; Wang, Fenghua; Sun, Xiaodong (Frontiers in Medicine, 2022)
Purpose: To compare the efficacy and safety of conbercept using a treat-and-extend (T&E) regimen versus a pro re nata (PRN) regimen in Chinese patients with neovascular age-related macular degeneration (nAMD). Methods: This was a randomized, multicenter, noninferiority study. After an initial loading phase of three consecutive monthly intravitreal injections of 0.5 mg Conbercept, the patients were treated to PRN or T&E regimen. The prespecified retreatment criteria was defined as a more than 5-letter decrease in BCVA from the previous visit or any evidence of new retinal hemorrhages, or the presence of any IRF and any SRF of more than 200 μm in height at the sub-foveal center. The primary outcome was the mean change in best-corrected visual acuity (BCVA) from baseline to 24 months, with a prespecified non-inferiority limit of -5 letters. Results: From July 2016 through August 2018, 141 participants were allocated and treated (T&E, n = 69; PRN, n = 72). About one fifth of the overall participants were dropped out during the 12-month follow-up (28/141, 19.9%), and about one thirds of the overall participants were lost during the 24-month follow-up (51/141, 36%). At 2 years, mean BCVA letter improvement was +4.0 in the T&E group vs +5.1 in the PRN group, and T&E regimen was not non-inferior to PRN regimen [difference , -1.169 letters; 95% confidence interval (CI): -6.864 4.526]. Subgroup analyses also demonstrate the similar results in PCV patients, naive patients and no-naive patients. The mean decrease in central subfield thickness were 180 ± 165 μm in the T&E group and 247 ± 230 μm in the PRN group, respectively. The patients in the PRN group had required significantly fewer injections than those in the T&E group (12.4 vs 14.6 injections, P = 0.041). The types and rates of adverse events were comparable in the two treatment groups. Conclusion: These findings suggest that the T&E regimen was not non-inferior to the PRN regimen in patients with nAMD in terms of BCVA outcomes through 24 months. Trial registration: ClinicalTrials.gov identifier, NCT02802657